Integrasi Digital Service Innovation dalam Kebijakan Dividen: Analisis Mediasi Ukuran terhadap Nilai Perusahaan Tobin's Q - Hasti Pramesti Kusnara; Herry Achmad Buchory Buchory; Rizky Ferari Oktavian Oktavian; Siti Wulansari Wulansari; Ignatius Oki Dewa Brata (Ma'soem University, 2026)
This study investigates the integration of Digital Service Innovation in dividend policy and its impact on firm value, measured by Tobin's Q, with firm size as a mediating variable. Employing Signaling Theory and Agency Theory as the theoretical underpinnings, this research addresses the